SMART ATTENDANCE MANAGEMENT SYSTEM WITH FACIAL RECOGNITION, PHYSICAL PRESENCE VERIFICATION, AND CENTRALIZED DATABASE INTEGRATION - Awais Gul Airij; Muhammad Hammad; Umair Hayat; Owais Ali Solangi; Hashim Dahri; Najeeb Ur Rehman Malik (Spectrum of Engineering Sciences, 2025)
The developed Smart Attendance Management System, hereinafter referred to as ‘the System’, addresses a limitation faced in Facial Recognition Systems (FRS), which often fails to authenticate physical presence during attendance marking. The system attempts to solve this problem by designing a solution that authenticates physical presence while attendance is being marked. The solution uses physiological signals, specifically the blinking of eyes, to indicate physical presence. The system marks attendance by first matching the images stored in its database with input images. Upon successful matches, the system looks for physical presence authentication. Attendance is marked successfully upon verification of physical presence. The attendance is recorded in a database for administrative reference. The designed system uses visual representations to interact with users during the entire process of attendance marking for both successful and unsuccessful marks. The system offers reliable attendance tracking by combining eye blinking detection with face recognition algorithms to provide a foolproof attendance management system.